2021
DOI: 10.1037/dhe0000151
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for underrepresented and misrepresented college students in service-learning classes: Supporting agents of change.

Abstract: When college-based service learning is examined, outcomes are often analyzed in a univariate framework, and participants tend to be White and middle class (if demographic information is given). This examination is a survey of 198 students who were primarily underrepresented and misrepresented students attending a Hispanic Serving Institution. The goal was to discern the relationships among service learning, social insights, academics, personal insights, and civic responsibility within a multivariate framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Limited definitions of success, such as those publicly reported by many institutions, are not only insufficient but are potentially harmful to underrepresented and misrepresented students. By underrepresented, we mean students who are members of a social group that are present in academia at a reduced rate, disproportionate to their presence in the U.S. population, primarily as a result of historic disparities in opportunities and resources (Langhout & Gordon, 2021; Pyne & Means, 2013). Alternatively, a social group may be represented physically in numbers consistent with their presence in the larger population, but this physical representation may not address the failure of the institution to incorporate their views and perspectives into the development of institutional norms and policies.…”
Section: Centering Latinx Students In Conceptualizing Student Successmentioning
confidence: 99%
“…Limited definitions of success, such as those publicly reported by many institutions, are not only insufficient but are potentially harmful to underrepresented and misrepresented students. By underrepresented, we mean students who are members of a social group that are present in academia at a reduced rate, disproportionate to their presence in the U.S. population, primarily as a result of historic disparities in opportunities and resources (Langhout & Gordon, 2021; Pyne & Means, 2013). Alternatively, a social group may be represented physically in numbers consistent with their presence in the larger population, but this physical representation may not address the failure of the institution to incorporate their views and perspectives into the development of institutional norms and policies.…”
Section: Centering Latinx Students In Conceptualizing Student Successmentioning
confidence: 99%
“…West and Simmons (2012) believe Latinx students may particularly benefit from service-learning courses, and Petrov (2013) theorizes that Latinx students may experience service-learning differently than other students. Latinx students are often presented with a unique set of challenge when entering college: a lack of generational knowledge, access to fewer educational resources, and coming from underfunded schools (Langhout & Gordon, 2019).…”
Section: Impacts Of Service-learningmentioning
confidence: 99%
“…Furthermore, SL courses may improve student engagement and retention in scientific fields like psychology. Langhout and Gordon (2019) suggested SL may be a particularly engaging approach for underrepresented and misrepresented students since it lessens the fissure between the university cultural community and the home cultural community. Similarly, Daniel and Mishra (2017) suggested that SL may relate to long-term retention in Science Technology Engineering, and Mathematics (STEM).…”
Section: Benefits Of Slmentioning
confidence: 99%